2012
DOI: 10.1371/journal.pgen.1002819
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Immunoglobulin Domain Proteins ZIG-5 and ZIG-8 Cooperate with L1CAM/SAX-7 to Maintain Nervous System Integrity

Abstract: During nervous system development, neuronal cell bodies and their axodendritic projections are precisely positioned through transiently expressed patterning cues. We show here that two neuronally expressed, secreted immunoglobulin (Ig) domain-containing proteins, ZIG-5 and ZIG-8, have no detectable role during embryonic nervous system development of the nematode Caenorhabditis elegans but are jointly required for neuronal soma and ventral cord axons to maintain their correct position throughout postembryonic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
8
30
0
Order By: Relevance
“…Also, the lumbar ganglion appears largely normal in unc-116/KHC mutants, indicating that the mechanisms that regulate position of the remainder of this ganglion are likely distinct. This is consistent with work from other groups describing mechanisms guiding these neurons (Sasakura et al 2005;Zhou et al 2008;Benard et al , 2012Zhou and Chen 2011;Johnson and Kramer 2012).…”
Section: Specificity Of the Unc-116/khc Pathwaysupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the lumbar ganglion appears largely normal in unc-116/KHC mutants, indicating that the mechanisms that regulate position of the remainder of this ganglion are likely distinct. This is consistent with work from other groups describing mechanisms guiding these neurons (Sasakura et al 2005;Zhou et al 2008;Benard et al , 2012Zhou and Chen 2011;Johnson and Kramer 2012).…”
Section: Specificity Of the Unc-116/khc Pathwaysupporting
confidence: 92%
“…VAB-8/KIF26B, a kinesin-like motor protein in Caenorhabditis elegans, also has a role in many posterior cell migrations (Wightman et al 1996;Wolf et al 1998) and likely acts upstream of UNC-40/DCC and SAX-3/Robo to localize these receptors (Levy-Strumpf and Culotti 2007).and synapses . These studies have implicated cell adhesion molecules, extracellular matrix components, and cytoskeletal proteins as playing a critical role in maintaining neuronal position (Sasakura et al 2005;Zhou et al 2008;Benard et al , 2012Zhou and Chen 2011;Johnson and Kramer 2012). It has been hypothesized that dedicated maintenance factors "glue" the nervous system together as well as "shield" neurons from disruptive cell migration signals .…”
mentioning
confidence: 99%
“…SAX-7 (L1CAM) is required to maintain the positions of certain neuronal cell bodies in response to mechanical forces when the animal is moving Sasakura et al 2005;Wang et al 2005). SAX-7/L1CAM is also required for correct positioning of the nerve ring , maintenance of axon position in the VNC (Bénard et al 2012), and navigation of D-type commissures (Wang et al 2005). SAX-7 is also involved in patterning of the highly branched PVD dendrites (Salzberg et al 2013), illustrating its pleiotropic functions in the nervous system.…”
Section: Receptors and Adhesion Moleculesmentioning
confidence: 99%
“…Thereafter the worm grows 100-fold in volume, yet axonal architecture and synaptic contacts are maintained (Benard and Hobert, 2009; Knight et al, 2002). Genetic studies have identified molecules required for the maintenance of axon positions during growth and movement, including L1-CAM, F-spondin, the FGF Receptor among others (Aurelio et al, 2002; Benard and Hobert, 2009; Benard et al, 2012; Benard et al, 2006; Bulow et al, 2004; Johnson and Kramer, 2012; Pocock et al, 2008; Sasakura et al, 2005; Woo et al, 2008). This work indicates two important features regarding the maintenance of nervous system architecture during development.…”
Section: Introductionmentioning
confidence: 99%